Effect of scan parameters and etching temperature on low‐destructive nanofabrication of quartz. (1st October 2013) - Song, Chenfei; Yu, Bingjun; Qian, Linmao
Abstract : Maskless and low‐destructive nanofabrication on quartz surface can be realised by friction‐induced selective etching. In this reported work, the effect of scan parameters and etching temperature on low‐destructive nanofabrication of quartz was studied. It was found that the etching thickness increased with the increase of the scan load and the number of scan cycles, but decreased with the scan speed. The wear of quartz did not help to increase the etching thickness. To limit the possible destruction, the scanning should be finished under low‐destructive conditions. Compared with single scanning under high load, repeated scanning under lower load was more beneficial for fabricating a deeper structure in a low‐destructive way. To improve the fabrication efficiency, faster scan speed and higher etching temperature were the preferential selection. Based on the optimisation of the fabrication parameters, various styles of nanostructures can be produced on the quartz surface. These results will help realise the controllable low‐destructive nanofabrication on quartz.